Phylogenetically Distant BABY BOOM Genes From Setaria italica Induce Parthenogenesis in Rice - Chahal, Lovepreet Singh; Conner, Joann A.; Ozias-Akins, Peggy (Frontiers in Plant Science, 2022)
The combination of apomixis and hybrid production is hailed as the holy grail of agriculture for the ability of apomixis to fix heterosis of F1 hybrids in succeeding generations, thereby eliminating the need for repeated crosses to produce F1 hybrids. Apomixis, asexual reproduction through seed, achieves this feat by circumventing two processes that are fundamental to sexual reproduction (meiosis and fertilization) and replacing them with apomeiosis and parthenogenesis, resulting in seed that are clonal to the maternal parent. Parthenogenesis, embryo development without fertilization, has been genetically engineered in rice, maize and pearl millet using PsASGR-BABY BOOM-like (PsASGR-BBML) transgenes and in rice using the OsBABY BOOM1 (OsBBM1) cDNA sequence when expressed under the control of egg cell-specific promoters. Phylogenetic analysis revealed that BABY BOOM (BBM)/BBML genes from monocots cluster within three different clades. The BBM/BBML genes shown to date to induce parthenogenesis cluster within clade 1 (the ASGR-BBML clade) along with orthologs from other monocot species such as Setaria italica. For this study, we tested the parthenogenetic potential of three BBM transgenes from S. italica, each a member of a different phylogenetic BBM clade. All transgenes were genomic constructs under the control of the AtDD45 egg cell-specific promoter. All SiBBM transgenes induced various levels of parthenogenetic embryo development, resulting in viable haploid T1 seedlings. Poor seed set and lower haploid seed production was characteristic of multiple transgenic lines. Results presented in this study illustrate that further functional characterization of BBMs in zygote/embryo development are warranted.